The influence of motivation, competence and discipline on employee performance - Tengku Ine Hendriana (Enrichment : Journal of Management, 2023)
Preliminary study results obtained findings that employee performance has not been optimal. Many factors encountered, allegedly the most dominant influence in terms of motivation, competence and discipline are still low. Therefore the problems formulated include: How motivation, competence and discipline. How much influence direct and indirect motivation, competence, and discipline on the performance of employees at the Department of HRD at PT.SanSan Saudaratex Jaya. The research method used is descriptive method of analysis and operation of the calculation using SPSS 22, done to the amount of 39 people made as respondents (survey). Data analysis techniques used are correlation analysis techniques that is to determine the degree of closeness relationship between research variables and Path Analysis Techniques (Path Analyst). The results as follows: 1). Motivation picture that is reaching average score 3,49 including good category; 2). The description of competence is reaching average score 3,64 including good category; 3). The description of the discipline of achieving an average score of 3.57 is in either category; 4). Performance description of employees that reached an average score of 3.61 is in either category; 5). The total effect of motivation on employee performance is 15.50%; 6). The influence of total competence on employee performance is 26.30%; 7). The total effect of discipline on employee performance is 42.50%; 8). The total influence of the three variables is 84.30%. The conclusion of this research is proved to have a significant influence motivation, competence and discipline on the performance of employees.